DEVELOPING A SUSTAINABLE TOURISM VILLAGE MODEL: AN EXPLORATORY STUDY - Lieli Suharti; Hani Sirine; Samuel Martono (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2023)
Studies on sustainable tourism villages (STV) development highlighted the role of community-based tourism (CBT) and social entrepreneurship (SE). Previous studies mostly focused on community and social entrepreneurship but neglected tourism management, which became the research gap of this study. The aim of this study was to investigate the contributions of CBT, SE, and tourism management in sustaining a tourism village. This study used a qualitative method, so the data were collected through focus group discussions and in-depth interviews with key players of Kaki Langit Mangunan Tourism Village, Yogyakarta. The results showed that the involvement and integration of CBT and SE were crucial in achieving STV. Finally, STV also required professionalism in management.